“Responsibility to Protect” as a Political and Legal Rationale of Uses of Force in International Relations - Stanislav Valentinovich Korostelev (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
This article explores the problem addressing the political and legal rationale of the “humanitarian intervention”. The right to perform “humanitarian intervention” is to be derived from moral obligations, and presumed as a resume of the universally agreed prohibition of gross violations of human rights. That right was termed as a “responsibility to protect”, and confessed by the international community as a political obligation, which did not come in contradiction with the law, rather than as a “law” if nothing else.